(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
United territorial communities (UTC) competitiveness is a key element in forming a strategic plan for their development. Therefore, the administrative and economic reform carried out in Ukraine should provide the necessary conditions for the formation and development of territorial communities. UTCs must operate in accordance with the principles of efficient management, it is necessary to take into account all the costs and benefits of implementing programs to develop their own competitiveness. This The result of the formation of such competitiveness is to increase the efficiency of territorial communities. The article considers the specifics of the formation of approaches to understanding the essence of UTC competitiveness, in particular – specifies the factors and factors influencing competitiveness. Peculiarities of interdependence of UTC development on the specifics of their regional territorial location are determined. Peculiarities of the current stage of reforming the system of local self-government, as well as the related transformation of the principles of economic policy of local governments in Ukraine, requires a review of all systemic factors that determine the functioning of the grassroots administrative and economic system. In this aspect, a fundamentally new, as well as a basic element of such a system are united territorial communities (UTC), which are formed in Ukraine in the process of implementing a new state policy – decentralization of local government and increasing the role of local communities in meeting their socio-economic development. Thus, the availability of a specific list of qualitative factors for assessing the competitiveness of UTC allows the local community to assess them and determine the number of parameters and based on this analysis to form a strategy to achieve the necessary competitiveness indicators, which will form a community development strategy. On the other hand, without access to a system for assessing and analyzing such parameters, local communities will not be able to set clear goals and objectives for investment or infrastructure development, which, of course, will not allow them to form an appropriate level of competitiveness